KAJIAN PERBAIKAN POSTUR KERJA DENGAN METODE OWAS (OVAKO WORKING POSTURE ANALYSIS SYSTEM) (Studi Kasus di Pabrik Roti Cimpago Putih) - meldia fitri; Widya Laila (Sekolah Tinggi Teknologi Industri Padang, 2017)
The roles of human as workers are still dominant in conducting production process, especially that related to manual activities. One of the humans rote is in the procss of displacing materials. These activities potentially raise various camplaints such as muscle pain and could cause accident at work. Pabrik Roti Cimpago Whit Bread still conduct MMH (Manual Materials Handling) activites in producing bread. These make the workers get low back pain. Theis research seeks to identify and evaluate inappropriate body posture at work and recommend safe body posture for the workers by using OWAS (Ovako Working Posture Analysis System). Analysis syetem through which 7 working posture were corrected of the 7, 4 posture were classified into category 2 suggerting that they were dangerous for musculoskeletal sytem and 3 postures were classified into category 3 indicating that they were unsafe for musculoskeletal and needed immediate repair. Keywords: work posture, OWAS, improvement work posture.